2013
DOI: 10.1186/1742-4755-10-57
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge of safe motherhood among women in rural communities in northern Nigeria: implications for maternal mortality reduction

Abstract: BackgroundMost developed countries have made considerable progress in addressing maternal mortality, but it appears that countries with high maternal mortality burdens like Nigeria have made little progress in improving maternal health outcomes despite emphasis by the Millennium Development Goals (MDGs). Knowledge about safe motherhood practices could help reduce pregnancy related health risks. This study examines knowledge of safe motherhood among women in selected rural communities in northern Nigeria.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
5
23
1
Order By: Relevance
“…This study revealed that 51(8.1%) who experienced obstetric danger signs 44(7.0%) had Good practice seek medical care when they faced problem. A study done in Indonesia, revealed that among the pregnant women who attended ANC, 36.6% of the respondents gave correct answers to a question on common practice such as, it is necessary to go to the hospital when severe headache or vision problems happen in pregnancy [11][12][13][14]. The difference might be due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that 51(8.1%) who experienced obstetric danger signs 44(7.0%) had Good practice seek medical care when they faced problem. A study done in Indonesia, revealed that among the pregnant women who attended ANC, 36.6% of the respondents gave correct answers to a question on common practice such as, it is necessary to go to the hospital when severe headache or vision problems happen in pregnancy [11][12][13][14]. The difference might be due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Knowledge of obstetric danger signs and birth preparedness enhance utilization of skilled care during childbirth, and emergency obstetric care services. [7] Previous studies have reported different prevalence of awareness of danger signs in different settings among pregnant women. [8,9] For example, Kabakyenga et al identified severe vaginal bleeding as the most mentioned complication by women during pregnancy (49%), childbirth (64%), and postpartum (57%) period.…”
Section: Introductionmentioning
confidence: 99%
“…An appreciable number of the women (38.3%) had attained tertiary education (Table 1). This is a marked improvement from the study of Okereke et al (2013), where less than 5% of the female respondents participating in their study (site also in Northern Nigeria) had attained tertiary education. Other researchers have observed a lower educational status for females in Northern Nigeria as compared to other regions of the country (Korode, 2008;African Girl-Child Education Initiative, 2001;Umar, 1996).…”
Section: Discussionmentioning
confidence: 89%